Child Neuropsychology Assessment and Interventions for Neurodevelopmental Disorders - Semrud-Clikeman, Margaret; Ellison, Phyllis Anne Teeter; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
During the past decade, significant advances have been made in the field of neurodevelopmental disorders, resulting in a considerable impact on conceptualization, diagnostics, and practice. The second edition of Child Neuropsychology: Assessment and Interventions for Neurodevelopmental Disorders brings readers up to speed clearly and authoritatively, offering the latest information on neuroimaging technologies, individual disorders, and effective treatment of children and adolescents. Starting with the basics of clinical child neuropsychology and functional anatomy, the authors present a transactional framework for assessment, diagnosis, and intervention. The book carefully links structure and function-and behavioral and biological science-for a more nuanced understanding of brain development and of pathologies as varied as pervasive developmental disorders, learning disabilities, neuromotor dysfunction, seizure disorders, and childhood cancers. This volume features a range of salient features valuable to students as well as novice and seasoned practitioners alike, including: Overview chapters that discuss the effects of biogenic and environmental factors on neurological functioning. New emphasis on multicultural/cross-cultural aspects of neuropsychology and assessment. Brand new chapters on interpretation, neuropsychological assessment process, and report writing. An integrative model of neurological, neuroradiological, and psychological assessment and diagnosis. Balanced coverage of behavioral, pharmacological, and educational approaches to treatment. Case studies illustrating typical and distinctive presentations and successful diagnosis, treatment planning, and intervention. Important practice updates, including the new HIPAA regulations. Child Neuropsychology, 2nd Edition, is vital reading for school, clinical child, and counseling psychologists as well as neuropsychologists. The book also provides rich background and practical material for graduate students entering these fields.
Anatomy and Physiology -- to Child Clinical Neuropsychology -- Functional Neuroanatomy -- Development in the CNS -- Electrophysiological and Neuroimaging Techniques in Neuropsychology -- Clinical Assessment -- Integrating Neurological, Neuroradiological, and Psychological Examinations in Neuropsychological Assessment -- Neuropsychological Domains of Functioning -- The Neuropsychological Assessment Process -- Neuropsychological Assessment Approaches and Diagnostic Procedures -- Childhood and Adolescent Disorders -- Neuropsychological Correlates of Childhood and Adolescent Psychiatric Disorders: Disruptive Behavior Disorders -- Neuropsychological Correlates of Childhood and Adolescent Internalized Disorders: Mood and Anxiety Disorders -- Autistic Spectrum Disorders -- Language-Related and Learning Disorders -- Metabolic, Biogenetic, Seizure, and Neuromotor Disorders of Childhood -- Acquired Neurological Disorders and Diseases of Childhood -- Childhood Cancer -- An Integration Intervention Paradigm -- Neuropsychological Intervention and Treatment Approaches for Childhood and Adolescent Disorders -- Pediatric Psychopharmacological and Combined Interventions -- Erratum.
Keywords: PHILOSOPHY (GENERAL).; PSYCHOLOGY, CLINICAL; DEVELOPMENTAL PSYCHOLOGY; PSYCHOLOGY; CHILD AND SCHOOL PSYCHOLOGY; NEUROPSYCHOLOGY